Acceptance and Strength of Electronic Documents as Proof in Malaysian Syariah Courts: (Penerimaan dan Kekuatan Dokumen Elektronik dalam Pembuktian Mahkamah Syariah di Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2016)
This article discusses the extent of the power and admissibility of electronic documents as a means of proof in Syariah courts in Malaysia. This study uses a quantitative approach. A questionnaire was given to respondents to determine how they perceived the admissibility of electronic documents as evidence in court. The respondents were staff of the Syariah courts and legal practitioners. In the respondents' perception, there is an urgent need to establish standard operating procedures (SOPs) or the verification of documents. At the same time, practitioners of Shariah law should be given adequate exposure and training related to electronic documents. Syariah courts should create joint ventures with agencies that have expertise in the field of electronic documents in order to improve their knowledge and thus make the Syariah court a respected body.Keywords: document, electronic, Syariah court, methods of proof